2017
DOI: 10.1016/j.ijdrr.2016.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Washington households' expected responses to lahar threat from Mt. Rainier

Abstract: This study examines households' risk perceptions and hazard adjustments through an investigation of the population at risk of lahars from the Mt. Rainier volcano. It is guided by a model in which demographic variables, locational variables, and past information search influence three psychological variables-risk perception, hazard intrusiveness, and affective response. In turn, these psychological variables along with locational and demographic variables influence three measures of household hazard adjustments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 91 publications
2
17
1
Order By: Relevance
“…Siegrist and Gutscher (2008) also suggest that the presence of an emotional response is not enough to persuade residents of flood-prone areas to mitigate. Similar to the results of this study, Wei and Lindell (2017) found affective response was not predictive of lahar preparedness of Mt. Rainier area residents.…”
Section: Emotionsupporting
confidence: 89%
“…Siegrist and Gutscher (2008) also suggest that the presence of an emotional response is not enough to persuade residents of flood-prone areas to mitigate. Similar to the results of this study, Wei and Lindell (2017) found affective response was not predictive of lahar preparedness of Mt. Rainier area residents.…”
Section: Emotionsupporting
confidence: 89%
“…Several researchers have examined the role of worry, the emotional component, in relation to preparedness. These authors argue that incorporating this component can be particularly relevant in complex and uncertain situations, in which attachment and emotions facilitate making risk assessments more quickly, easily, and efficiently (Slovic, Finucane, Peters, & MacGregor, 2004; Terpstra, 2011; Wei & Lindell, 2017). Previous studies have found that negative emotions, such as worry and anxiety, increase levels of risk perception (Bradford et al., 2012; Ho et al., 2008; Wei & Lindell, 2017; Weinstein, Lyon, Rothman, & Cuite, 2000) but can also be distinct constructs that should be evaluated using different measures.…”
Section: Introductionmentioning
confidence: 99%
“…Risk research from multiple hazards has shown that effect was an important factor in individual's perceptions of risk [36,37] and subsequent action. In Wei and Lindell [38], threat perception in the PADM was measured by expected personal consequences, hazard intrusiveness and affect. They found that the measures were significantly correlated with each other and that people who expect greater personal consequences think and talk about the hazard more frequently and have greater negative affect.…”
Section: Protective Action Decision Modelmentioning
confidence: 99%